The influence of bank size on profitability: An application of statistics - Tharu, Nanda Kumar; Shrestha, Yogesh Man (Goodwood Publishing, 2019)
Purpose: The main purpose of this study is to determine and evaluate the effects of bank size on the profitability of commercial banks in Nepal. Research Methodology: This study has been adopted as panel research design. 8 sample banks adopted from 28 banks using simple random sampling. The time series data between the period of 2013AD and 2018AD has been treated. The data source was Nepal Rastra Bank. Descriptive and inferential statistics were used as statistical tools. SPSS Version 20 was used for data analysis. Finding: The results of different tests proved that the profitability (ROA) has not been significantly influenced by size of the bank (Assets). Limitation: This study does not deal to those factors which help to establish this existing relationship. Contribution: These findings could be very significant information for Nepalese commercial bank officers and shareholders of these banks and policy builders advocating merger; to peep through once. Keywords: Bank size, Profitability, Return on equity, Nepalese commercial banks.